2005
DOI: 10.1111/j.1365-4632.2005.02447.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of vitiligo with broadband ultraviolet B and vitamins

Abstract: Background  While oral psoralen plus ultraviolet A (PUVA) remains the most popular therapeutic modality for vitiligo, recent reports have shown that narrowband ultraviolet B (UVB) also induces significant repigmentation. In this study we evaluated the efficacy of broadband UVB on actively spreading, progressive vitiligo in patients who had been followed for many months (12 or more) in our practice, who continued to depigment despite treatment. Methods  Nine patients with actively spreading vitiligo were expose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…Little definitive evidence purports the use of BB-UVB in vitiligo, primarily due to the dominant and successful use of NB-UVB. BB-UVB with vitamin supplementation was found to be effective in actively spreading vitiligo for inducing repigmentation when given 2-3 times weekly for 6-8 weeks (Don, Iuga et al, 2006). Although the role of vitamin supplementation was not substantiated in the outcome, this particular trial suggests that BB-UVB can be an effective treatment for vitiligo (Don, Iuga et al, 2006).…”
Section: Bb-uvb Phototherapymentioning
confidence: 95%
See 2 more Smart Citations
“…Little definitive evidence purports the use of BB-UVB in vitiligo, primarily due to the dominant and successful use of NB-UVB. BB-UVB with vitamin supplementation was found to be effective in actively spreading vitiligo for inducing repigmentation when given 2-3 times weekly for 6-8 weeks (Don, Iuga et al, 2006). Although the role of vitamin supplementation was not substantiated in the outcome, this particular trial suggests that BB-UVB can be an effective treatment for vitiligo (Don, Iuga et al, 2006).…”
Section: Bb-uvb Phototherapymentioning
confidence: 95%
“…BB-UVB with vitamin supplementation was found to be effective in actively spreading vitiligo for inducing repigmentation when given 2-3 times weekly for 6-8 weeks (Don, Iuga et al, 2006). Although the role of vitamin supplementation was not substantiated in the outcome, this particular trial suggests that BB-UVB can be an effective treatment for vitiligo (Don, Iuga et al, 2006). Targeted BB-UVB and MEL were found to have nearly equal rates and degrees of repigmentation when evaluated after 8 treatments (Asawanonda, Kijluakiat et al, 2008).…”
Section: Bb-uvb Phototherapymentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have investigated the use of vitamins E, C, B12, and folic acid, and most have either shown statistically insignificant improvements when compared to UV therapy alone or no improvement at all. [46][47][48] One study compared the use of a combination of antioxidants containing vitamins C and E, alpha lipoic acid, polyunsaturated fatty acids, and cysteine monohydrate, and found it to give significantly increased repigmentation when used in conjunction with NB-UVB when compared towing NB-UVB alone. [49] Plant immunomodulators, such as Polypodium leucomotos, were originally used as a method of protecting against the phototoxic characteristics of UV therapy.…”
Section: Adjuvant Therapymentioning
confidence: 99%
“…Lin et al demonstrate an increase in protection against UVinduced damage after oral administration of vitamin E combined with vitamin C [19] (Table 3). Studies demonstrate; oral vit E has shown to increase narrow band-UVB effectiveness in vitiligo patients [20].…”
Section: Vitamin Ementioning
confidence: 99%